2020
DOI: 10.1038/s41598-020-59085-1
|View full text |Cite
|
Sign up to set email alerts
|

The oxytocin-prostaglandins pathways in the horse (Equus caballus) placenta during pregnancy, physiological parturition, and parturition with fetal membrane retention

Abstract: Despite their importance in mammalian reproduction, substances in the oxytocin-prostaglandins pathways have not been investigated in the horse placenta during most of pregnancy and parturition. Therefore, we quantified placental content of oxytocin (OXT), oxytocin receptor (OXTR), and prostaglandin E2 and F2 alpha during days 90-240 of pregnancy (PREG), physiological parturition (PHYS), and parturition with fetal membrane retention (FMR) in heavy draft horses (PREG = 13, pHYS = 11, FMR = 10). We also quantifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 69 publications
0
3
0
2
Order By: Relevance
“…Gene expression of IL-1β and IL-6 (as well as protein expression of IL-6) was also increased in retained allantochorions (Jaworska & Janowski 2019). Gene expression of prostaglandin endoperoxide synthase-2 (PTGS2), involved in prostaglandin production, was however decreased in retained placenta which could contribute to the observed imbalance in inflammatory processes and tissue remodelling in this pathology (Rapacz-Leonard et al 2020). Finally, protein expression of oxytocin receptors (OXTR) was greatly reduced in retained placentas in case of secondary atony, but this difference was not observed in retained allantochorion without secondary atony (Rapacz-Leonard et al 2015b.…”
Section: Placental Retentionmentioning
confidence: 99%
“…Gene expression of IL-1β and IL-6 (as well as protein expression of IL-6) was also increased in retained allantochorions (Jaworska & Janowski 2019). Gene expression of prostaglandin endoperoxide synthase-2 (PTGS2), involved in prostaglandin production, was however decreased in retained placenta which could contribute to the observed imbalance in inflammatory processes and tissue remodelling in this pathology (Rapacz-Leonard et al 2020). Finally, protein expression of oxytocin receptors (OXTR) was greatly reduced in retained placentas in case of secondary atony, but this difference was not observed in retained allantochorion without secondary atony (Rapacz-Leonard et al 2015b.…”
Section: Placental Retentionmentioning
confidence: 99%
“…Podczas ciąży u klaczy ekspresja tego enzymu hamowana jest poprzez wysoki poziom pregnanów, głównie 5α-dihydroprogesteronu (DHP) (44). Podczas porodu, wraz ze spadkiem syntezy pregnanów (8), enzym ten ulega wzmożonej ekspresji (54,66). Zgodnie z najnowszymi wynikami, ekspresja PTGS2 w momencie wydalenia płodu jest istotnie niższa u klaczy, u których w ciągu najbliższych 3 godzin rozwinie się zatrzymanie błon płodowych (ryc.…”
Section: Ryc 1 Ekspresja Białka Mhc-i W Tkankach łOżyska Klaczyunclassified
“…Dane użyte do przygotowania ryciny zostały opublikowane (54) i zdeponowane w publicznym repozytorium danych pod adresem https://doi.org/10.5061/dryad.fbg79cnr4 jak i same regulują jej przebieg (6,40,59,67). Jest to zgodne z innymi doniesieniami (26,27,54) o zaburzeniach szlaku syntezy prozapalnej u klaczy z zatrzymaniem błon płodowych (ryc. 3).…”
Section: Ryc 1 Ekspresja Białka Mhc-i W Tkankach łOżyska Klaczyunclassified
“…In mares, there is a positive feedback loop during luteolysis and parturition involving oxytocin, OXTR and endometrial PGF2α secretion [ 18 , 19 , 20 ]. De Ruijter-Villani and co-authors (2015) reported in D14 pregnant mare endometria that downregulation of the PGF receptor intercepted the oxytocin-prostaglandin F feedback loop [ 21 ].…”
Section: Introductionmentioning
confidence: 99%